2004
DOI: 10.1088/1742-5468/2004/09/p09004
|View full text |Cite
|
Sign up to set email alerts
|

Circuits in random graphs: from local trees to global loops

Abstract: Abstract. We compute the number of circuits and of loops with multiple crossings in random regular graphs. We discuss the importance of this issue for the validity of the cavity approach. On the one side we obtain analytic results for the infinite volume limit in agreement with existing exact results. On the other side we implement a counting algorithm, enumerate circuits at finite N and draw some general conclusions about the finite N behavior of the circuits. IntroductionThe study of random graphs, initiate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
46
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 24 publications
(51 reference statements)
2
46
0
Order By: Relevance
“…Characteristic motifs in a graph and degree correlations are in many real graphs not independent phenomena but they depend on each other as it has been shown for small (up to maximal connectivity) size subgraphs in [11,10,12,13]. Last but not least, it has been observed that the distribution of loop sizes is intimately connected with the thermal properties of lattice models defined on that graph [18,17]. On the other hand, the analytic approach to these models relies on the assumption that locally a random graph can be considered to have a tree like structure [19,20,21], i.e.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Characteristic motifs in a graph and degree correlations are in many real graphs not independent phenomena but they depend on each other as it has been shown for small (up to maximal connectivity) size subgraphs in [11,10,12,13]. Last but not least, it has been observed that the distribution of loop sizes is intimately connected with the thermal properties of lattice models defined on that graph [18,17]. On the other hand, the analytic approach to these models relies on the assumption that locally a random graph can be considered to have a tree like structure [19,20,21], i.e.…”
mentioning
confidence: 92%
“…where ℓ = L/N and σ(ℓ) is a function having the maximum at ℓ max = c/(c + 1) whose expression can be found in the literature [16,17]. Regarding Hamilton cycles, i.e.…”
mentioning
confidence: 99%
“…[13][7] [10] In complex networks, loops are both generic and abundant. [15][14] While short loops of length L ≪ N (where N is the network size) are rare in large random networks, ones with L ln N occur generically in numbers growing exponentially with N . Their number also grows roughly exponentially with L up to a maximum at a length L m ∼ N.…”
mentioning
confidence: 99%
“…For example, ER graphs with finite average connectivity have a finite number of finite loops [4,7]. On the contrary scale-free graphs have a number of finite loops which increases with the number N of vertices, provided that γ ≤ 3 [8,9].…”
mentioning
confidence: 99%